STUDI EKSPERIMENTAL PENGARUH PENGGUNAAN KALSIUM KARBONAT (CaCO3) SEBAGAI FILLER DALAM CAMPURAN LAPIS PERMUKAAN ASPAL PORUS TERHADAP KARAKTERISTIK MARSHALL - Ricardho Tri Wiranto; Stevy Thioritz; Mursalim (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Atma Jaya Makassar, 2023)
Porous asphalt is a type of asphalt that has special characteristics that allow it to absorb water and drain it into the lower pavement layer, because of its ability to reduce water pooling on the road surface. This research aims to determine the comparison of porous asphalt mixture characteristics based on Marshall testing with Japanese standards by varying the asphalt content with 5 different variations. There are two research methods used: Testing the asphalt characteristics based on the General Specification of Bina Marga Year 2018 Revision 2 Division 6 regarding asphalt pavement, and aggregate gradation and Marshall Test based on Japan Road Association (JRA). The Marshall Test is also divided into two tests: Conventional Marshall and Immersion Marshall. The research results indicate that Japanese standard porous asphalt, based on the VIM and stability, shows that porous asphalt mixture with Portland cement filler performs better compared to the one with CaCO3 filler, as it yields higher stability and fewer air voids. The percentage of OAC (Optimum Asphalt Content) obtained using CaCO3 filler is 4%.